INFLUÊNCIA DA ÁREA DE ESTRUTURA EM AÇO EXPOSTA NO DESEMPENHO TÉRMICO DE EDIFICAÇÕES - Caetano, Lucas Fonseca; Souza, Henor Artur de; Gomes, Adriano Pinto (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
When a material with high thermal conductivity, such as steel, is placed in parallel with a less conductive material, most of the heat transfer occurs through the steel by conduction, characterizing an effect known as thermal bridging through the steel profile or exposed structure. The thermal bridge reduces the thermal resistance of the closings and increases energy costs for environmental heating or cooling. Taking into account these considerations, this paper aims to evaluate the thermal performance of naturally ventilated and artificially conditioned environments by means of computational simulations using the EnergyPlus program. The results show that there was an increase of about 12,5% in the building energy consumption considering a typical summer design day as a function of the exposed steel area of the building structure. There was a maximum increase of 10,6% in the environment total thermal cooling load, evidencing that the larger the exposed steel area in the building closed system, the greater the effect caused by this thermal bridge.